Implementation of Tepak Sirih dance performance to Deli Malay culture - Adawiyah, Rabiatul (Arbain Publishing, 2024)
This research aims to determine the implementation of the betel tepak offering dance to the Malay culture of deli. Descriptive qualitative research methods with a review of rivew literature. Based on research findings. (1) The cultural customs in the palace have a close relationship with the culture that develops among the people. The elements of Islamic culture that came to the Malays were not exclusive to the court but developed widely into popular culture. (2) Betel nut dance is still often performed in large events to welcome guests. Therefore, this dance is also called the welcome dance.